Desenvolvimento de uma metodologia para determinação da estereoquímica dos alcaloides piperidínicos de Senna spectabilis utilizando o naproxeno como reagente de derivatização quiral - Cytrângolo, Isabela Lopes e (2025)
The homologous pair (–)-cassine and (–)-spectaline was isolated from Senna spectabilis as major metabolites and has demonstrated biological activity as antimalarial, anti-chikungunya, and acetylcholinesterase inhibitors, an enzyme related to Alzheimer's disease. They are classified as piperidinic and chiral alkaloids, making the understanding of their stereochemistry relevant and necessary for advancing studies on their potential as drug candidates. Thus, a methodology was developed aiming for efficiency and low cost to determine the stereochemistry of these compounds through the preparation of Mosher esters, using the chiral derivatization reagent (S)-naproxen. The homologous mixture was resolved using chromatographic techniques, including high-performance liquid chromatography, and the (S)-naproxen was extracted from commercial pharmaceutical formulations, as this drug is marketed in an enantiomerically pure form, which was confirmed by polarimetry. Since the Mosher technique, which involves double derivatization, requires both (S)-naproxen and (R) naproxen, it was necessary to racemize the former in an acidic medium to obtain the enantiomeric pair. Subsequently, the esters were prepared using the racemic mixture of naproxen, based on the Steglich esterification reaction, with the resulting diastereoisomeric products being separated and confirmed by preparative thin-layer chromatography and mass spectrometry, respectively. To determine the absolute configurations of the Mosher esters, computational calculations were also performed based on Born-Oppenheimer molecular dynamics, to assist in understanding the conformers, evaluate how the piperidine ring substituents (equatorial/axial) are arranged, and assess the anisotropic effect of the naphthyl group (protection/deprotection) on the substituents adjacent to the asymmetric carbon of the hydroxyl group.